Microempreendedor individual: uma análise sobre a importância da contabilidade para o crescimento e consolidação do empreendimento em Caicó/RN - Simões, Franciedia Santos (2015)
In the search for formalisation of the micro-enterprises in Brazil, in 2008 was sanctioned supplementary law No. 128 that instituted the Microempreendedor Individual and brought a lot of changes and advancements for micro and small businesses, contributing to the reduction of informality. Knowing that accounting is essential for enterprises and accounting knowledge is a crucial instrument in making decisions and in providing useful information for the development of your business the present work had as objective to analyze if the perception of the Individual Entrepreneur from the city of Caicó RN accounting is important to the growth and consolidation of its enterprise , showing the features of MEI, demonstrating the importance of accounting for the companies by checking if the MEI uses accounting for decision making, and to ascertain their perspectives with respect to your business. The methodology used was the field research through a data collection done by means of a questionnaire applied to 2.9% sample of MEIS. Due to the large size of accounting science and the risk that the project runs without the use of its services if it justifies the interest in whether the perception of MEI accounting is important to the development and consolidation of your company. Being that this category of entrepreneurs think the books important to your business, but don't use it for decision making.